Splinting in horizontal root fractures: A Bayesian network meta-analysis - Tatiana Carvalho Kowaltschuk; Flávio Magno Gonçalves; Bianca Marques de Mattos de Araujo; Natália Teixeira da Silva Cruz; Angela Graciela Deliga Schroder; Bruna Belz Antoniazzi; Everdan Carneiro; Marisa Nogueira Alencar; Ulisses Xavier da Silva-Neto; Odilon Guariza-Filho; Cristiano Miranda de Araujo; Vânia Portela Ditzel Westphalen (PLoS ONE, 2025)
Objective This study aims to evaluate which splinting method offers the most favorable prognosis in cases of dental trauma involving horizontal intra-alveolar root fractures. Materials and methods Search strategies were adapted for seven electronic databases and gray literature to identify studies evaluating the prognosis of horizontal intra-alveolar root fractures based on the type of splint used. The risk of bias in the included studies was assessed using the Joanna Briggs Institute Critical Appraisal tools. A Bayesian network meta-analysis was conducted. Results A total of 3,174 references were retrieved, of which six studies met the inclusion criteria. No significant differences were found between the types of splints used and the healing outcomes of horizontally fractured intra-alveolar roots, including comparisons to cases without fixation. Across all studies, the degree of fragment displacement was a key factor influencing healing: the less displacement, the better the prognosis. Other treatment-related variables analyzed by the authors also played a role in determining tooth prognosis. Conclusions There may be no difference regarding the type of splint used when considering the healing of horizontal intra-alveolar root fractures; however, other factors may have influenced this outcome. Clinical Relevance Understanding the fracture characteristics and the type of splinting intervention employed is essential for ensuring appropriate treatment in such cases.